PENETAPAN HARGA POKOK PRODUKSI DENGAN PENDEKATAN FULL COSTING SEBAGAI DASAR PENENTUAN HARGA JUAL - adrian abdul Wahid (Universitas Prof.Hazairin,SH Bengkulu, 2021)
Calculation of the cost of production can be done with two approaches, namely the full costing approach and variable costing. In this study, the approach to calculating the cost of production using a full costing approach was carried out at UKM Telur Gulung Raos. This study uses a qualitative method with a descriptive analysis approach. The results of this study, the cost of production with the company's approach of Rp. 398,916.96 and the calculation of the cost of production with the full costing approach of Rp. 533,207.16. The calculation is generated from the number of products 580 products in a period of one day. on the original dining menu of Rp. 398.61 with a selling price of Rp. 1000. On the original egg roll menu, according to the company, it is Rp. 398.61 with a selling price of Rp. 1000 and with a full costing approach of Rp. 629.52 with a selling price of Rp. 1,499.10. On the egg roll menu, according to the company, cilor rolls are Rp. 437.61 with a selling price of Rp. 1000 and with a full costing approach of Rp. 668.52 with a selling price of Rp. According to the company, the egg roll vermicelli menu is Rp. 448.61 with a selling price of Rp. 1000 and with a full costing approach of Rp. 679.52 with a selling price of Rp. Rp. 1,452.84. According to the company, the egg roll otak-otak menu is Rp. 798.60 with a selling price of Rp. 2000 and with a full costing approach of Rp. 1,029.52 with a selling price of Rp. 2,537.14. On the egg roll sausage menu, according to the company, it is Rp. 1,358.61 with a selling price of Rp. 2000 and with a full costing approach of Rp. 1,589.52. with a selling price of Rp2,325.19